2019
DOI: 10.3390/w11112266
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Bias Correction Methods to Assess the Impact of Climate Change on Flood Frequency Curves

Abstract: Climate projections provided by EURO-CORDEX predict changes in annual maximum series of daily rainfall in the future in some areas of Spain because of climate change. Precipitation and temperature projections supplied by climate models do not usually fit exactly the statistical properties of the observed time series in the control period. Bias correction methods are used to reduce such errors. This paper seeks to find the most adequate bias correction techniques for temperature and precipitation projections th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…In order to correct this and to improve the performance of the model, the rainfall dataset for HadGEM2-ES was bias-corrected. Bias correction is the process of scaling climate model outputs to account for their systematic errors, in order to improve their fitting to observations [35]. The evaluation of other climatic parameters shows satisfactory results as the biases are close to zero and NSE is greater than 0.7, so they were not bias corrected.…”
Section: Bias Correction Of Projected Rainfallmentioning
confidence: 99%
“…In order to correct this and to improve the performance of the model, the rainfall dataset for HadGEM2-ES was bias-corrected. Bias correction is the process of scaling climate model outputs to account for their systematic errors, in order to improve their fitting to observations [35]. The evaluation of other climatic parameters shows satisfactory results as the biases are close to zero and NSE is greater than 0.7, so they were not bias corrected.…”
Section: Bias Correction Of Projected Rainfallmentioning
confidence: 99%
“…Similar studies have identified climate models as being the dominant source (e.g. Sulis et al, 2012;Hattermann et al, 2018). Indeed, Addor et al (2014) highlight that there seems to be a general agreement in the literature on the dominant contribution of climate models to the uncertainty in discharge projections.…”
Section: Discussionmentioning
confidence: 53%
“…Joseph et al (2018) also considered hydrological parameters (VIC) and climate models (RCP) uncertainty assessment in seasonal flow projections. Soriano et al (2019) evaluated the uncertainty of bias correction methods on flood frequency and found that the climate model's bias correction is significant and brought significant change in the magnitude of flood design values. Feng and Beighley (2020) also identified the uncertainties from both climate forcings and hydrologic model components as well as associated parameterization.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the biases correction of GCMs output was applied on a grid commensurate with daily climate model output. Nowadays, many researchers have been used and addressed the importance of climate bias correction methods (Kay et al 2009;Saini et al 2015;Soriano et al 2019). Quantile mapping, empirical mapping, simple statistical transformation, and joint probability are the most popular and widely applied for climate model bias correction and related to observed climate time series.…”
Section: Introductionmentioning
confidence: 99%